Isolation and preliminary characterization of extracellular vesicles from bottlenose dolphin (Tursiops truncatus) and long-finned pilot whale (Globicephala melas) blow - Valentina Moccia; Cinzia Centelleghe; Andrea Zendrini; Selene Tassoni; Luca Ceolotto; Bertrand Bouchard; Eva Álvarez; Gaia Pesce; Paolo Bergese; Annalisa Radeghieri; Sandro Mazzariol; Valentina Zappulli (PLoS ONE, 2026)
Cetaceans are key sentinel species for environmental health monitoring. Although sampling from free-ranging animals is challenging, the analysis of cetacean blow offers a minimally invasive approach to assess their health status. Extracellular vesicles (EVs) are cell-derived nanostructures present in biological fluids and widely studied as disease biomarkers in humans. Despite the potential for similar uses, EVs have not been studied in cetacean blow to date. This proof-of-concept study aims to assess the feasibility of the isolation and characterization of EVs from blow samples collected from five bottlenose dolphins ( Tursiops truncatus ) kept under human care and from a free ranging specimen of long-finned pilot whale ( Globicephala melas ). EVs were purified from bottlenose dolphin blows by ultracentrifugation (UC) or size exclusion chromatography (SEC) and from the long-finned pilot whale by SEC. Particle concentration and size distribution were assessed by Nanoparticle Tracking Analysis (NTA), morphology by Air-atomic force microscopy (AFM) and protein expression by Western Blotting (WB). NTA revealed a higher mean particle concentration in bottlenose dolphin EVs isolated by UC compared to SEC, while EVs isolated from the long-finned pilot whale presented a lower particle concentration. AFM confirmed the presence of EV-like particles within the typical EV size range in bottlenose dolphin’s EVs obtained both by SEC or UC. All EV samples were positive for CD9 and integrin-β and negative to Calnexin. SEC was more sensitive to detect OmpA, a membrane protein of Gram-negative bacteria, in EVs from both species. Our pilot study demonstrates that EV-like particles are present in cetacean blow and can be isolated and characterized. Future investigations focused on characterizing and quantifying a wider array of EV associated molecules may further the application of blow EV analysis for cetacean health assessments.